Integrating nascent organisations. On the settlement of the European External Action Service. Issue 1 (2nd January 2017) - Riddervold, Marianne; Trondal, Jarle
Abstract: This study shows how the EU's new Common Foreign and Security policy (CFSP) administration – the European External Action Service (EEAS) – experienced early organisational settlement. We find that the EEAS acts relatively independently from member-state governments, suggesting administrative autonomy. It is also relatively integrated into the Commission structure, suggesting inter-institutional integration of sub-units in the two institutions. Important lessons can be learned. For organisation theory: Firstly, nascent organisations are likely to experience some degree of 'settlement' after birth by establishing ties towards organisations from which they originate. Secondly, settlement is influenced by pre-existing organisational capacity and recent organisational history. For the CFSP literature: Firstly, the CFSP has indeed developed beyond intergovernmental cooperation; we might be witnessing a 'normalisation' or 'communitarisation' of CFSP policy- processes. Secondly, cooperation and further institutionalisation of relations between the EEAS and the Commission may be key factors in explaining integration within the CFSP.